Dislocation of a dual mobility total hip replacement following fracture of the polyethylene liner - Vedrine, Bertrand; Guillaumot, Pierre; Chancrin, Jean-Luc (Veterinary and Comparative Orthopaedics and Traumatology, 2016)
An eight-year-old male English Setter was referred for management of a dislocation of a cemented dual mobility canine total hip prosthesis that occurred four months after the initial surgery. Revision surgery showed that the dislocation was associated with fracture of the ultra-high molecular weight polyethylene liner. The dislocation was successfully reduced after replacing the liner. A dual mobility acetabular component is composed of a mobile polyethylene liner inside a metallic cemented cup. Chronic wear of the components of a canine dual mobility total hip replacement has not been described previously. The use of this type of implant is fairly recent and limited long term follow-up of the implanted cases may be the explanation. Acute rupture of a polyethylene liner has never been described in humans, the only case of rupture of a polyethylene liner occurred 10 years after implantation. The case presented here of rupture of the polyethylene liner of a dual mobility total hip replacement is a hitherto unreported failure mode in this model of acetabular cup in the dog.
Keywords: Hip; replacement; prosthesis; dual mobility; dislocation